Kerusakan Hati Akibat Keracunan Alkohol Berulang pada Tikus Wistar (LIVER DAMAGE DUE TO ALCOHOL INTOXICATION REPEAT IN WISTAR RATS) - Suaniti, Ni Made; Djelantik, Anak Agung Gede Sudewa; Suastika, Ketut; Astawa, Nyoman Mantik (Jurnal Veteriner; Vol 13 No 2 (2012), 2013)
The aims of this study was to determine the liver damage from alcohol intoxication in Wistar rats.The design used in this study was a randomized true experimental post test only control group design. Thestudy used 15 rats divided into 3 treatment groups each of which consists of 5 rats. The first group wasgiven distill water. The second group was given 5% alcohol, and the third group was given 20% alcohol. Ratswere treated with alcohol daily for six weeks. Biochemical markers were detected the levels of aldehydedehydrogenase (ALDH) in serum and histological changes in liver tissue. ALDH is a biochemical markerof a sensitive and specific ethanol after chronic alcohol administration. Blood sample was collected at 6and 24 hours after the last peroral administration of repeated alcohol treatment, and serum levels ofALDH was tested by enzyme linked immunosorbent assay (ELISA). The results showed that the levels ofALDH in the blood of alcohol treated Wistar rats significantly higher as compared to those of control rats.ALDH levels increased by 83.11% after administration of 5% alcohol and 112.05% after administration of20% taken after 6 hours of alcohol for 6 weeks. On samples taken after 24 hours, ALDH levels by 95.11%after administration of 5% alcohol and 86.79% after administration of 20% alcohol. Oral treatment with20% alcohol chronically was led to changes in the microscopic structure (necrosis) of liver tissue in Wistarrats. Liver tissue damage occured due to repeated use of alcohol is accompanied by increasing serum levelsof ALDH in Wistar rats.
Keywords: Liver damage, aldehyde dehydrogenase, alcohol, Wistar rats